Correlations of gait kinematics and cognitive skills in Parkinson disease - Joshua J. Lander; Matthew F. Moran; Hannah R. Alexanian (PLoS ONE, 2025)
Cognitive impairments and gait disturbances are often concurrent in Parkinson disease (PD), but the extent to which specific cognitive deficits relate to gait abnormalities remains unclear, especially in early-stage PD. To address this gap, we conducted an observational correlational study to determine if cognitive performance in distinct domains is associated with gait kinematics in PD. This study included a cohort of 19 individuals with early-stage PD who underwent gait analysis with a three-dimensional marker-less motion capture system (Theia Markerless Inc., Kingston, ON, CA) during three conditions: single-task walking, cognitive dual-task walking, and the Timed Up and Go (TUG) test. Cognitive abilities were assessed using computerized tests (Creyos, Toronto, ON, CA) of working memory (WM), response inhibition (RI), and mental rotation (MR). We found that higher WM scores significantly correlated with better gait performance under dual-task conditions, including faster gait velocity (r = 0.6524, p = 0.0025), longer stride length (r = 0.6758, p = 0.0015), higher toe clearance (r = 0.5234, p = 0.0215), and greater hip range of motion (ROM) (r = 0.6803, p = 0.0014). Similarly, better MR ability was associated with longer stride length (r = 0.5178, p = 0.0231) and greater hip ROM (r = 0.4886, p = 0.0338) during dual-task walking. Furthermore, superior WM and MR performance were linked to faster TUG completion times, particularly during the second walking phase of the TUG (WM: r = −0.682, p = 0.0013; MR: r = −0.6755, p = 0.002). These results indicate that WM and MR may be linked to gait performance in PD, especially during cognitively challenging walking tasks. These findings may have clinical, rehabilitative, and neuroscientific utility for those involved in the study and management of PD.